2015
DOI: 10.12816/0017913
|View full text |Cite
|
Sign up to set email alerts
|

Sand-Fly Phlebotomus Papatasi ( Phlebotominae ) : A General Review with Special Reference to Zoonotic Cutaneous Leishmaniasis in Egypt

Abstract: Leishmania are digenetic protozoa which inhabit two hosts, the sandfly where they grow as promastigotes in the gut, and the mammalian macrophage where they grow as amastigotes. Sandfly (or sand fly) is a colloquial name for any species or genus of flying, biting, bloodsucking Dipteran encountered in sandy areas. In the United States, sandfly may refer to certain horse flies that are also known as "greenheads" (family Tabanidae), or to members of the family Ceratopogonidae, also known in Florida and elsewhere a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Majority of clinical and epide miologic studies on Toscana virus were reported from Italy, France, Spain, Portugal and other Mediterranean countries as Kuwait, Tehran, Turkey…etc (Kadanalı, 2012). Phlebotomus species are well known in all the Mediterranean Countries (Saleh et al, 2015). The update data on TOSV circulation in the Mediterranean Countries, so in Bosnia and Herzegovina raises concern about potential implications for blood donations, because of the asymptomatic course of illness in majority of cases.…”
Section: Review and Discussionmentioning
confidence: 99%
“…Majority of clinical and epide miologic studies on Toscana virus were reported from Italy, France, Spain, Portugal and other Mediterranean countries as Kuwait, Tehran, Turkey…etc (Kadanalı, 2012). Phlebotomus species are well known in all the Mediterranean Countries (Saleh et al, 2015). The update data on TOSV circulation in the Mediterranean Countries, so in Bosnia and Herzegovina raises concern about potential implications for blood donations, because of the asymptomatic course of illness in majority of cases.…”
Section: Review and Discussionmentioning
confidence: 99%
“…They showed that a-the seasonal activity started in April and ended in November or beginning of December, b-female outnumbered male indoors (7.4:1) and vise-versa was outdoors (0.14:1), c-blood fed females were 97.7% indoors and 29.4% outdoors, d-nocturnal activity between 6 p.m. to 6 a.m. indoors and 8 p.m. to 6 a.m. outdoors and e-sand-fly immature stages were recovered from the rodent burrows and poultry sheds. Saleh et al (2015) stated the prevalent of ZCL in Sinai Peninsula with at least three identified foci.…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, the ZCL is a public health threatened to Egypt, particularly Sinai Peninsula. Two ZCL foci were identified in North Sinai (Faris et al, 1988) and presence of Egyptian ZCL patient manifested as diffuse CL (Morsy et al, 1997) at least nine species sandflies were encountered in Sinai (El Sawaf et al, 1987) and the Nile Delta (Morsy et al, 1990) as well as allover many Egyptian areas (Saleh et al, 2015). Among these sand-flies were P. papatasii (Scopoli), the vector of ZCL (Wahba et al, 1990) and P. sergenti, the vector of ACL (Hanafi et al, 2001).…”
Section: Methodsmentioning
confidence: 99%